2019
DOI: 10.3390/ijms20020431
|View full text |Cite
|
Sign up to set email alerts
|

Non-Targeted Metabolomics Reveals Sorghum Rhizosphere-Associated Exudates are Influenced by the Belowground Interaction of Substrate and Sorghum Genotype

Abstract: Root exudation is an important plant process by which roots release small molecules into the rhizosphere that serve in overall plant functioning. Yet, there is a major gap in our knowledge in translating plant root exudation in artificial systems (i.e., hydroponics, sterile media) to crops, specifically for soils expected in field conditions. Sorghum (Sorghum bicolor L. Moench) root exudation was determined using both ultra-performance liquid chromatography and gas chromatography mass spectrometry-based non-ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(25 citation statements)
references
References 76 publications
1
24
0
Order By: Relevance
“…pectic acid) 15 17 . The amount of carbon (C) released into the rhizosphere greatly depends on the plant species, the genotype, the age, the chemical-physical-biological soil characteristics and biotic or abiotic stresses 18 20 . To cope with P deficiency, the major metabolites that plants release from their roots are organic acids (e.g .…”
Section: Introductionmentioning
confidence: 99%
“…pectic acid) 15 17 . The amount of carbon (C) released into the rhizosphere greatly depends on the plant species, the genotype, the age, the chemical-physical-biological soil characteristics and biotic or abiotic stresses 18 20 . To cope with P deficiency, the major metabolites that plants release from their roots are organic acids (e.g .…”
Section: Introductionmentioning
confidence: 99%
“…In this study, exudates were collected from roots with rhizosphere substrate still attached. The largest difference in this dataset was observed between soil-grown and sand- or clay-grown plants, which might be explained by soil-derived metabolites co-extracted with root exudates (Sasse et al, 2018; Miller et al, 2019). The authors showed some ions to be specifically up- or down-regulated in exudates of clay- vs. sand-grown plants, but their effect was not strong enough to separate the two conditions in a principal component analysis (Miller et al, 2019), which might be due to their exudate collection method, which was a mixture between the in situ and in vitro conditions utilized here.…”
Section: Discussionmentioning
confidence: 95%
“…4). A recent study found differences in sorghum exudates of plants grown in clay, sand, and soil (Miller et al, 2019). In this study, exudates were collected from roots with rhizosphere substrate still attached.…”
Section: Discussionmentioning
confidence: 99%
“…Plant metabolomics mainly concerns metabolic analysis and metabolite fingerprinting of single plants, in which the metabolites in plant organs and tissues are qualitatively and quantitatively analyzed. In addition, metabolomics is used to compare and identify plants of the same species but different genotypes and to study the interaction between plants and herbivores, including the effects of plant defense metabolites on herbivore genotypes and resistance [17][18][19][20][21][22][23][24][25][26]. In this work, metabolomics was used to analyze the quality and metabolic changes in tender coconut during storage after harvest, and the important reasons for the deterioration of coconut were revealed, thus providing a theoretical basis for the preservation of fresh coconut after harvest.…”
Section: Introductionmentioning
confidence: 99%